A Woman's Calling (London : National Association of Local Government Officers)
1937 1937 1930s 13 pages 2. The General Nursing Councils to be urged to :— (a) divide the preliminary state examination into two parts : Part I, Anatomy, Physiology and Hygiene ; and Part II, Theory and Practice of Nursing. (b) agree to the examination for Part I being taken prior to entry for general training. (c) require all hospitals recognised as complete training schools to admit probationer nurses at age 17-18 years to a three years’ course. (d) require all hospitals recognised as complete training schools to make an allowance for time spent in any form of approved preliminary training, provided satisfactory evidence of such training is produced. (e) limit the questions in the final state examinations for all parts of the register to nursing treatment ; neither systematic medicine, surgery, gynaecology, or psychiatry to be included. 3. Local Authorities to be urged to staff hospitals which are not approved as training centres by the General Nursing Councils, with trained nurses who shall not be required to perform domestic duties. 4. Local Authorities to be urged to arrange for nurses to be released from all duties at least on the night before as well as on the day of examinations. 5. Local Authorities to be urged to afford ample facilities in the way of leave of absence (with pay) and maintenance grants, where necessary, for post-graduate candidates for specialised appointments. N.A.L.G.O. Proposals on Salaries and Service Conditions Nursing is a profession requiring the highest degree of skill and devotion to duty. In the past women have sacrificed their health and strength in the cause of humanity with no hope of adequate reward. It should not have been so. The profession deserves, and must have, a more generous recognition of its services. Many authorities have made beneficial changes in the salaries and working conditions of nursing staffs in the past few years, but over the whole field there is still much room for improvement. The shortage of nurses is attributable, in part, to the fact that improvements in their working conditions are a vital necessity if the service is to attract girls all of whom, in private life, enjoy a freedom unknown 25 years ago. There is still far too much regimentation in the staff administration. Discipline and the authority of a senior on duty can be maintained without dominance ; off duty a comradeship which should exist amongst all grades of staff with a common purpose in life is all too often lost in the retention of the dignity of official designations. On the vexed question of salaries and general conditions of service, N.A.L.G.O. submits its revised programme :— 6 292/54.73/2/1